COVID‐19 in transplant recipients: The Spanish experience. Issue 5 (10th November 2020) - Coll, Elisabeth; Fernández‐Ruiz, Mario; Sánchez‐Álvarez, J. Emilio; Martínez‐Fernández, José R.; Crespo, Marta; Gayoso, Jorge; Bada‐Bosch, Teresa; Oppenheimer, Federico; Moreso, Francesc; López‐Oliva, María O.; Melilli, Edoardo; Rodríguez‐Ferrero, Marisa L.; et al.
Abstract : We report the nationwide experience with solid organ transplant (SOT) and hematopoietic stem cell transplant (HSCT) recipients diagnosed with coronavirus disease 2019 (COVID‐19) in Spain until 13 July 2020. We compiled information for 778 (423 kidney, 113 HSCT, 110 liver, 69 heart, 54 lung, 8 pancreas, 1 multivisceral) recipients. Median age at diagnosis was 61 years (interquartile range [IQR]: 52‐70), and 66% were male. The incidence of COVID‐19 in SOT recipients was two‐fold higher compared to the Spanish general population. The median interval from transplantation was 59 months (IQR: 18‐131). Infection was hospital‐acquired in 13% of cases. No donor‐derived COVID‐19 was suspected. Most patients (89%) were admitted to the hospital. Therapies included hydroxychloroquine (84%), azithromycin (53%), protease inhibitors (37%), and interferon‐β (5%), whereas immunomodulation was based on corticosteroids (41%) and tocilizumab (21%). Adjustment of immunosuppression was performed in 85% of patients. At the time of analysis, complete follow‐up was available from 652 patients. Acute respiratory distress syndrome occurred in 35% of patients. Ultimately, 174 (27%) patients died. In univariate analysis, risk factors for death were lung transplantation (odds ratio [OR]: 2.5; 95% CI: 1.4‐4.6), age >60 years (OR: 3.7; 95% CI: 2.5‐5.5), and hospital‐acquired COVID‐19 (OR: 3.0; 95% CI: 1.9‐4.9). Abstract : The authors report the Spanish nationwide experience with solid organ and hematopoietic stem cell transplant recipients diagnosed with COVID‐19, revealing a higher incidence and more aggressive course of infection than in the general population.